Environment‐strategy coalignment: An empirical test of its performance implications - Venkatraman, N.; Prescott, John E. (Strategic Management Journal, 1990)
Abstract The positive performance impact of a coalignment between the environment and strategy of a business is an important theoretical proposition in strategic management. In spite of its importance and intuitive appeal, the extent of empirical support is equivocal and riddled with problems of conceptualizing and testing for coalignment. This paper evaluates alternate approaches to testing such a proposition and argues in favor of specifying coalignment as ‘profile deviation’, which states that coalignment is the degree to which strategic resource deployments adhere to an ‘ideal profile’ for a given environment. Subsequently, this proposition is tested across two time periods, and eight distinct environments in two different samples drawn from the PIMS data base. Results, which were generally robust across the two periods, strongly support the proposition of a positive performance impact of environment‐strategy coalignment. Implications and research directions are developed.